Prognostic value of exercise capacity among men undergoing pharmacologic treatment for erectile dysfunction: The FIT Project - Same, Robert V. (Clin Cardiol, 2017)
BACKGROUND: Vascular erectile dysfunction (ED) has been identified as a potentially useful risk factor for predicting future cardiovascular events, particularly in younger men. Because these men typically score more favorably on traditional cardiovascular disease risk assessment tools, there exists a gap in knowledge for how to most appropriately identify those men who would benefit from more aggressive treatments. To date, no studies have examined the impact of fitness on cardiovascular outcomes in men with ED. This study sought to examine the prognostic impact of maximal exercise capacity on cardiovascular‐related outcomes in men ages 40 to 60 years being treated for ED. HYPOTHESIS: We hypothesized that there would be an independent association between higher baseline fitness level and lower cardiovascular events. METHODS: We analyzed 1152 men with pharmacy claims file–confirmed active pharmacologic treatment for ED from the Henry Ford Exercise Testing (FIT) Project (1991–2009). All patients were free of coronary heart disease and heart failure, and underwent clinician‐referred exercise stress testing, with fitness measured in metabolic equivalents of task (METs). Multivariable Cox proportional hazard models adjusted for traditional cardiovascular risk factors were used to study the association between fitness and all‐cause mortality, major adverse cardiovascular events (MACE) (defined as myocardial infarction or revascularization), and incident type 2 diabetes mellitus. RESULTS: The mean age of the population was 53 years, with 39% African Americans. In multivariable analysis, each 1 MET of fitness was associated with a 16% lower risk of death (hazard ratio [HR]: 0.84, 95% confidence interval [CI]: 0.76‐0.94, P = 0.002), and a nonsignificant reduction in MACE (HR: 0.89, 95% CI: 0.79‐1.003, P = 0.048), and incident diabetes (HR: 0.92, 95% CI: 0.85‐1.01, P = 0.129). CONCLUSIONS: Higher baseline fitness is associated with improved cardiovascular prognosis in a population of middle‐aged men treated for ED.